Analyzing Teacher’s Set Induction And Closure In An EFL Classroom: A Case Study At MI Tarbiyah Islamiyah Palembang - Egina Aprida; Renny Kurnia Sari; Hariana Amalia (Institute of Advanced Knowledge and Science, 2026)
This study aimed to analyze the implementation of set induction and closure strategies in an English as a Foreign Language (EFL) classroom and to examine students’ responses toward these instructional practices. This research employed a qualitative case study design involving one English teacher and nine elementary students at MI Tarbiyah Islamiyah Palembang. Data were collected through classroom observations, semi-structured interviews, and documentation to ensure data triangulation. The findings revealed that set induction was consistently implemented through greeting, questioning, and interactive activities such as games, songs, and quizzes, which significantly enhanced students’ engagement and readiness. However, closure strategies were implemented less consistently and often lacked reflective depth. Students generally showed positive responses, including increased motivation and participation, although differences in ability influenced engagement levels. The study concluded that the effectiveness of instructional strategies depends not only on their implementation but also on consistency, classroom conditions, and teacher adaptability.